Alat bukti elektronik dalam penanganan tindak pidana kepabeanan - Efendi, Saparudin; Abadi, Sukma Hidayat Kurnia (Institute for Advanced Science, Social, and Sustainable Future, 2024)
This article will explain that international trade is part of the customs system and takes place in the customs area. Customs is a special type of crime that is regulated by a separate law outside the Criminal Code. Customs is a special criminal offense regulated by law outside the Criminal Code (KUHP). This special customs criminal law is regulated in a separate law outside the general criminal law contained in the Criminal Code. This special criminal offense is regulated in law outside of general criminal law separately, and rapid progress in the field of information and communication technology has led to the development of modern transactions via electronic media. Advances in information and communication technology, which have led to the development of modern transactions via electronic media, in connection with increasingly rapid technological advances, will of course give rise to a new social order. Recognized evidence (KUHAP) of course also makes digital or electronic evidence difficult to accept, as well as proving the defendant's guilt on the grounds that digital evidence has not been fully regulated in the Criminal Procedure Code (KUHAP), forms of action that can be categorized as criminal acts in the field of customs, and the legal force of proof using electronic evidence. This research uses normative methods, namely, conducting research on problems through an approach to legislation by examining statutory regulations.